Clinical Pharmacokinetics of Atogepant in Healthy Japanese and White Adults - Ramesh R. Boinpally; Brian McNamee (Neurology and Therapy)
Abstract Introduction Atogepant is a calcitonin gene-related peptide receptor antagonist approved for the preventive treatment of migraine in adults in the USA, EU, and several other countries. The objectives of this study were to evaluate the pharmacokinetics (PK) and dose proportionality of atogepant in healthy Japanese participants, evaluate the safety and tolerability of atogepant in Japanese participants, and explore the differences in the PK and safety of atogepant in Japanese vs white participants. Methods A total of 50 participants (40 Japanese and 10 white) were enrolled into five cohorts; Japanese cohorts were randomized in a 4:1 ratio to atogepant (10 mg, 30 mg, or 60 mg daily dosing and 60 mg twice daily) or placebo. The white participants were randomized to atogepant (60 mg twice daily) or placebo. Doses were administered on day 1 and days 3–8, with those on days 1 and 8 administered after an overnight fast. Results In Japanese participants, atogepant exposure increased with dose, and there was no accumulation with once-daily dosing and minimal (~ 20%) accumulation with twice-daily dosing. Atogepant steady-state exposure appeared to be marginally lower in Japanese participants compared with white participants and was well tolerated. There were no treatment-related adverse events, serious adverse events, clinically significant changes in vital signs, or signs of suicidal ideation or behaviors. Conclusion Atogepant exposure increased with dose in healthy Japanese participants and was well tolerated within the dose range tested.